Agricultural value chain exhibition links Ethiopian actors - Alemayehu, N. (International Livestock Research Institute, 2011)
On March 31, 2011, IPMS and the Oromia Bureau of Agriculture organized an exhibition on Agricultural Value Chains in Bishoftu/Debrezeit. In this video, Nigatu Alemayehu tells us why the exhibition is needed and who partcipated. The main objective of the exhibition was to transfer knowledge between input suppliers, technology generators, market agents and service providers.